Synthesis and characterization of interpenetrating polymeric networks based bio-composite alginate film: A well-designed drug delivery platform - Ghosal, Kajal; Das, Arijit; Kumar Das, Sanjoy; Mahmood, Syed; Ramadan, Mohamed Abdel Monem; Thomas, Sabu (Elsevier Ltd, 2019)
This study aimed to develop and characterize the calcium alginate films loaded with diclofenac sodium and other hydrophilic polymers with different degrees of cross-linking obtained by external gelation process. To the formed films different physicochemical evaluation were performed which showed an initial character of the films. The films produced by this external gelation process were found thicker (0.031–0.038 mm) and stronger (51.9–52.9 MPa) but less elastic (2.3%) than those non-cross-linked films (0.029 mm; 39.7 MPa; 4.4%). The lower water vapor permeability (WVP) values of the films were obtained where maximum level of crosslinking occurs. Composite films can be cross-linked in presence of external crosslinking agent to improve the quality of the produced matrices for various uses. The characterization of the film was performed using Differential Scanning Calorimetry (DSC) and Fourier-Transform Infrared Spectroscopy (FT-IR) analysis. The Scanning Electron Microscopy (SEM) study showed the morphology of treated composite films. The kinetic release studies showed a sustained release of the drug from the formulated films as it can be prolonged in composite film. The prepared biodegradable Ca-Alginate bio-composite film may be of clinical importance for its therapeutic benefit.